A Novel Frameshift Mutation in KAT6A Is Associated with Pancraniosynostosis - Marji, Fady P.; Hall, Jennifer A.; Anstadt, Erin; Madan-Khetarpal, Suneeta; Goldstein, Jesse A.; Losee, Joseph E. (Journal of Pediatric Genetics, 2020)
De novo heterozygous mutations in the KAT6A gene give rise to a distinct intellectual disability syndrome, with features including speech delay, cardiac anomalies, craniofacial dysmorphisms, and craniosynostosis. Here, we reported a 16-year-old girl with a novel pathogenic variant of the KAT6A gene. She is the first case to possess pancraniosynostosis, a rare suture fusion pattern, affecting all her major cranial sutures. The diagnosis of KAT6A syndrome is established via recognition of its inherent phenotypic features and the utilization of whole exome sequencing. Thorough craniofacial evaluation is imperative, craniosynostosis may require operative intervention, the delay of which may be detrimental.
Keywords: KAT6A syndrome; whole exome sequencing; pancraniosynostosis